COOPERATION IN LOGISTICS TECHNOLOGY RESEARCH: HOW TWINNING PROJECT AFFECTS R+D IN THE FIELD OF LOGISTIC SYSTEMS AND NETWORKS - Bányai, Tamás; Illés, Béla; Landschützer, Christian; Schenk, Fabian; Massi, Flavien (Advanced Logistic Systems - Theory and Practice, 2019)
The overall aim of the UMi-TWINN project was to reinforce the scientific excellence and innovation capacity in logistic systems of the University of Miskolc and its high-quality twinning partners for the benefit of different industries and logistics markets. To boost twinning partners' scientific excellence and innovation capacity in logistics technologies, as well as implementing a research and innovation strategy we have focused on the following three sub-topics: design of logistic systems and networks, intelligent transport systems and dynamical analysis of materials handling machines. Within the frame of this paper the authors describe the main results in the field of design of logistic systems.